If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -52 + -3 = 3x + 20 Combine like terms: -52 + -3 = -55 -55 = 3x + 20 Reorder the terms: -55 = 20 + 3x Solving -55 = 20 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -55 + -3x = 20 + 3x + -3x Combine like terms: 3x + -3x = 0 -55 + -3x = 20 + 0 -55 + -3x = 20 Add '55' to each side of the equation. -55 + 55 + -3x = 20 + 55 Combine like terms: -55 + 55 = 0 0 + -3x = 20 + 55 -3x = 20 + 55 Combine like terms: 20 + 55 = 75 -3x = 75 Divide each side by '-3'. x = -25 Simplifying x = -25
| 2x+15=63-5x | | 6x+5-3x=18+4x | | 1.2=2.5-3b | | 16x^2+16x-1=0 | | 4x^2+6=13 | | C-6=-22 | | x(x+10)+25=0 | | -4(x-5)=12(x+3) | | 6(2x-1)=-11(x+1) | | -2y+3x=2 | | 12x-2y=8 | | 4x+4x=8 | | -9r+5=-28 | | 0.4(y+3)=0.5(y-4) | | 5m+(2m+1)=23 | | 0+50*1-60-60*0+10=10 | | 2+4x=26-x | | 9(m+1)=6m | | 3.49x=78 | | 6x-14=-2x+26 | | x-4=3x-8 | | 3.49+x=78 | | y-2x=6 | | 2x-(4x-12)=3+x | | A+6=22 | | -11*-9= | | 10+1s=30 | | 3+3(2t-3)-3(4t+3)-7= | | -11*9= | | 3+3(2t-3)-(4t+3)-7= | | 6*x=216 | | 5x^2-x-4x^2-12=0 |